2018
DOI: 10.1002/aur.1956
|View full text |Cite
|
Sign up to set email alerts
|

Parenting adolescents with ASD: A multimethod study

Abstract: A number of studies have concluded that parents of children with ASD experience high levels of parenting stress. However, little is known about their parenting behaviors. Especially parenting in adolescence remains under investigated, although this period is associated with additional challenges for both adolescents and their parents. In this study, 44 adolescents with ASD and a control group of 38 adolescents without ASD, aged 12-16 years old, participated together with their mother. We compared parenting beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…We found that during the conflictual interaction, parents exhibited more positive parenting behaviors, that is, were more sensitive and less intrusive toward their adolescents' with ASD, compared to the parents of TD adolescents. These findings replicated an observational study, indicating that mothers of adolescents with ASD exhibit more sensitivity while handling a conflict, compared to mothers of TD adolescents (van Esch et al, 2018]. Our findings also correspond with reports of mothers to children with and without ASD [Maljaars et al, 2014].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We found that during the conflictual interaction, parents exhibited more positive parenting behaviors, that is, were more sensitive and less intrusive toward their adolescents' with ASD, compared to the parents of TD adolescents. These findings replicated an observational study, indicating that mothers of adolescents with ASD exhibit more sensitivity while handling a conflict, compared to mothers of TD adolescents (van Esch et al, 2018]. Our findings also correspond with reports of mothers to children with and without ASD [Maljaars et al, 2014].…”
Section: Discussionsupporting
confidence: 89%
“…These studies addressed the parent-child relationship within a positive or neutral interaction. A recent study, which examined parent-adolescent interaction during a conflictual interaction revealed that mothers of adolescents with ASD were involved in a more sensitive and empathic way when handling a conflict with their adolescent child, compared to mothers of TD adolescents [van Esch, Vanmarcke, Ceulemans, Van Leeuwen, & Noens, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…The present study built upon the study of van Esch, Vanmarcke, et al (2018) in which parenting behaviours were compared between the ASD and the general population control group (GPC). All adolescents were between 12 and 16 years old.…”
Section: Methods Participantsmentioning
confidence: 99%
“…These findings suggest that parenting ASD children might disproportionately require sensitivity and warmth. Indeed, a recent multi-method study exploring parent-child interactions in 44 adolescents with ASD and 38 matched controls suggested that mothers of ASD adolescents showed more sensitivity and creativity when engaging their child in a structured task (van Esch et al 2018).…”
Section: Parenting and Problem Behaviour In Asdmentioning
confidence: 99%